2016
DOI: 10.11613/bm.2016.039
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the analytical performances of Capillarys 2 Flex Piercing, Tosoh HLC-723 G8, Premier Hb9210, and Roche Cobas c501 Tina-quant Gen 2 analyzers for HbA1c determination

Abstract: IntroductionHaemoglobin A1c (HbA1c) is widely used in the management of diabetes. Therefore, the reliability and comparability among different analytical methods for its detection have become very important.Materials and methodsA comparative evaluation of the analytical performances (precision, linearity, accuracy, method comparison, and interferences including bilirubin, triglyceride, cholesterol, labile HbA1c (LA1c), vitamin C, aspirin, fetal haemoglobin (HbF), and haemoglobin E (Hb E)) were performed on Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The β-thalassemia is characterized by variable increases in HbF and unusually high HbA 2 concentrations. Our previous study found that an increased proportion of HbF could affect the HbA 1c results using Capillarys 2FP ( 5 ). Thus, the β-thalassemia intermedia/major sample with highly elevated HbF (> 10%) could interfere the HbA 1c measurement by Capillarys 2FP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The β-thalassemia is characterized by variable increases in HbF and unusually high HbA 2 concentrations. Our previous study found that an increased proportion of HbF could affect the HbA 1c results using Capillarys 2FP ( 5 ). Thus, the β-thalassemia intermedia/major sample with highly elevated HbF (> 10%) could interfere the HbA 1c measurement by Capillarys 2FP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that HbA 1c concentrations measured by Capillarys 2FP system in normal samples, without haemoglobinopathies, showed high correlation and concordance with those obtained using a boronate affinity high-performance liquid chromatography (HPLC) system, i.e. Premier Hb9210 (Trinity Biotech Plc, Bray, Ireland) ( 5 ). Further accuracy verification demonstrated a great consistency with International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference method (HPLC/CE) values ( 5 ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The precision was evaluated according to the EP15-A2 protocol of the Clinical and Laboratory Standards Institute (CLSI) [17]. The original reference and 1:16 predilution were analyzed three times per day during a period of five consecutive workdays(n = 15 per level).…”
mentioning
confidence: 99%